Closure of defunctioning loop ileostomy is associated with considerable morbidity. (27th March 2013) - Sharma, A.; Deeb, A.‐P.; Rickles, A. S.; Iannuzzi, J. C.; Monson, J. R. T.; Fleming, F. J.
Abstract Aim An elective defunctioning ileostomy is commonly employed to attenuate the morbidity that may arise from distal anastomotic leakage. The magnitude of risk associated with subsequent ileostomy closure is difficult to estimate as many of the data arise from small series. This study looked at the rate of complications and predictive factors in a large series of patients. Methods The National Surgical Quality Improvement Program database was queried for patients who had an elective closure of ileostomy between 2005 and 2010. Patient demographics, preoperative risk factors and operative variables were recorded. The primary outcome was occurrence of major (mortality, sepsis, return to the operating room, renal failure, major cardiac, neurological or respiratory episode) or minor (wound infection, urinary tract infection) complications within 30 days. Univariate and multivariate regression was used to evaluate the effect of these clinical factors on the complication rate. Results In total, 5401 patients underwent closure of ileostomy, of whom 502 (9.3%) patients had major complications. The incidence of minor complications was 8.4% (452 patients). There were 32 (0.6%) deaths. American Society of Anesthesiologists grade, functional status, prolonged operative time, history of chronic obstructive pulmonary disease, dialysis and disseminated cancer were independent predictors of major complications. There was no significant increase in complication rates in patients over the age of 80. Major complications were associated with a significant increase in postoperative stay (13.9 vs 4.7 days, P < 0.0001). Conclusion Closure of ileostomy is associated with a significant complication rate. It may use as many resources as the primary surgery and is not a minor follow‐up operation.